PLLA/Fibrin Tubular Scaffold: A New Way for Reliable Endothelial Cell Seeding. (12th May 2014) - Rigogliuso, Salvatrice; Carfì Pavia, Francesco; La Carrubba, Vincenzo; Brucato, Valerio; Ghersi, Giulio
Abstract : In the present work a simple and quick technique for cell seeding into tubular-shaped scaffolds, which allows a homogeneous cell distribution, was tested. The poly-L-lactide (PLLA) scaffolds, prepared via diffusion induced phase separation (DIPS), were filled with fibrin gel in order to obtain a hybrid scaffold for Vascular Tissue Engineering applications. The formation of immobilized fibrin networks on the inner surface of the tubular scaffolds was observed using confocal microscopy and SEM. Morphological analysis of the so-obtained scaffold revealed that the fibrin gel is uniformly distributed on the internal surface of the scaffold, leading to an organized structure. Moreover a penetration of the gel into the porous wall of the scaffold was observed. The in vitro endothelial cell cultures carried out in the scaffolds highlighted a faster cell proliferation inside the hybrid scaffold with respect to simple PLLA scaffold. Results show that the fibrin/PLLA hybrid scaffold may be favourably used for Vascular Tissue Engineering applications.